The Role of the Particle po- in the Comparison of Adjectives in Shtokavian Dialects - Trifunović, Aleksandar (Balcania et Slavia)
The use of the particle po- with adjectives (and also adverbs) in either positive or comparative or even superlative form is fairly well present in Slavic languages. In Slovak for example, it is mostly used with terms for colours, carrying the meaning ʽlessʼ or ʽsomewhatʼ e.g. pobelavý ʽwhitish, somewhat whiteʼ ʽblackish, somewhat blackʼ, while in Czech it can either modify the meaning similar to that in Slovak e.g. pobělavý ʽwhitish, somewhat whiteʼ, or can be used with a comparative degree, carrying the meaning ʽless, slightly lessʼ e.g. postarší člověk ʽslightly less old manʼ. On the other hand, in Russian, it carries the meaning »more, even, slightly more, even more«, e.g. поинтереснее ʽeven more interestingʼ, постарша ʽeven olderʼ. At the very south of the Slavic language territory, i.e. in the Macedonian and Bulgarian languages, the use of the particle po- is the only mean of forming comparative degree of adjectives.   In the Shtokavian dialects, the usage of the particle po- with adjectives consists of the whole spectrum of meaning. In some dialects it can be used with the positive degree e.g. povisok ʽpretty highʼ, the comparative degree e.g. poviši ʽa bit higher / a bit less highʼ - so the meaning can be the same as in Czech or Russian, depending on the dialect - and even superlative degree of an adjective ponajviši ʽhighest of the highestʼ. And on the other hand, there are dialects in which this is the only way of forming the comparative degree of adjectives – the same as in Macedonian and Bulgarian.   In this article, all the variants of the usage of the particle po- in the Shtokavian dialects are presented, with the idea to establish the border between dialects that use this particle and those which do not use it. A substantial effort was put in order to find if there is any parallel between the shift from synthetic type of comparison to the analytic one in these dialects. This in return could shed a light in the further research of the same phenomenon in Bulgarian and Macedonian languages.